Analisis Intervensi Psikososial Perkawinan Anak Korban Kekerasan Seksual: Studi Kasus Kabupaten Malang - Marwinata, Pepy; Hakim, Muhammad Nur Rizal (Sharia Journal and Education Center Publishing, 2025)
The aim of this research is to analyze the psychosocial psychology of child marriages which are victims of sexual violence. The approach in this research uses a qualitative descriptive method using interviews, observation and documentation as data collection techniques. This approach aims to obtain descriptive text or verbal form from sources directly in the field. In terms of psychosocial theory, it is a term used to describe the relationship between a person's social condition and their mental or emotional health. For example, the relationship between the fear a person has (psychological) and how he interacts with other people in his social environment. A person who has a healthy mentality will react in a positive way in various situations. In contrast to people who have mental instability, they will react negatively to everything that happens in life. The results of research conducted by researchers related to the psychosocial conditions of the impact of child marriage in Malang Regency are difficulty in adjusting, the range of experiencing household disputes, resolving problems with divorce, poor social relations, ways to educate children who are not yet competent and economic problems, then we can provide a solution to this problem through psychosocial intervention in the form of personal, group, familial and play therapy which will have a positive impact in the form of cognitive, emotional, behavioral and social environmental changes.